Basic Introduction to Pegon Writing at MTs Walisongo 2 students Krandegan Hamlet, Sukomakmur Village, Kajoran District, Magelang Regency - Abdun Nafi'; Titis Rosowulan; Dakusta Puspitasari (Universitas Nurul Jadid, 2024)
Learning to read and write in Arabic Pegon is not just a skill reserved for students in Islamic boarding schools, but it can also be an additional insight for students who have never learned it or are unfamiliar with it. The purpose of introducing the basics of Pegon writing is to facilitate students in understanding the yellow books (traditional Islamic texts). Additionally, this activity aims to cultivate students' enthusiasm for embracing the traditions of scholars and Islamic boarding schools, so they are not easily influenced by foreign cultures with their Latin language instruments. This community service adopted the ABCD approach, which consists of five main stages: Discovery, Dream, Design, Define, and Destiny. As a result of the learning activities provided with the ABCD approach, students were able to master the patterns of Pegon Arabic writing and apply them in understanding the texts according to the existing rules, as well as read them correctly. Thus, the introduction to basic Pegon writing at Walisongo 2 Junior High School served as an initial foundation for seventh-grade students to master the skills of reading and writing Arabic Pegon, enabling them to be prepared to study yellow books such as Fiqh, Tajwid, and Tauhid. Consequently, in the following grades, seventh-grade students will find it easier to understand yellow books both in reading and writing